2017
DOI: 10.1136/bmjopen-2016-014326
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the adoption of Schwartz Center Rounds as an organisational innovation to improve staff well-being in England, 2009–2015

Abstract: ObjectivesSchwartz Center Rounds (‘Rounds’) are a multidisciplinary forum in which healthcare staff within an organisation discuss the psychological, emotional and social challenges associated with their work in a confidential and safe environment. Implemented in over 375 North American organisations, since 2009, they have been increasingly adopted in England. This study aimed to establish how many and what types of organisations have adopted Rounds in England, and to explore why they did so.SettingPublic heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 15 publications
3
51
0
Order By: Relevance
“…Therefore, additional strategies need to be identified and implemented. Apart from some wider system issues—including those relating to race and ethnicity—that require further investigation and addressing by nurse educators and clinical leaders and managers, it is important that space for reflection is provided through, for instance, Schwartz rounds (Robert et al, ), and that routes to appropriate psychological support are visible and available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional strategies need to be identified and implemented. Apart from some wider system issues—including those relating to race and ethnicity—that require further investigation and addressing by nurse educators and clinical leaders and managers, it is important that space for reflection is provided through, for instance, Schwartz rounds (Robert et al, ), and that routes to appropriate psychological support are visible and available.…”
Section: Resultsmentioning
confidence: 99%
“…As articulating feelings in such environments comes with difficulty (Allan, ), it is important to put an appropriate structure in place. This could, for instance, be provided through Schwartz rounds, in which healthcare professionals discuss challenging cases and emotional aspects of their work (Robert et al, ). An evaluation of Schwartz rounds (Maben et al, ) showed that they led to a greater understanding, empathy and tolerance towards both colleagues and patients.…”
Section: Discussionmentioning
confidence: 99%
“…MedsIQ was founded in response to increasing awareness that children and young people are frequently harmed by errors in their medication. Children are 3 times more likely than adults to be harmed by medication errors and it has been shown that up to 15% of inpatient prescriptions have errors on them (1). What is MedsIQ?…”
Section: Development Of a Bronchiolitis Assessment Tool In Two Busy Umentioning
confidence: 99%
“…ARM such as imperforate anus are commonly overlooked on newborn examination. 21% of cases in Ireland are late diagnoses 1 . Delayed diagnosis is associated with significant morbidity and mortality.…”
mentioning
confidence: 99%
“…At a broader organisational level, grand rounds can include a growth mindset presentation. Furthermore, an increasing number of hospitals are holding Schwartz Rounds, which provide opportunities for all staff across varying disciplines and levels to share and understand the emotional challenges that clinicians and managers experience in providing clinical care and services 21. A growth mindset approach to coping with these challenges could be integrated into these sessions.…”
Section: Shifting Mindsetsmentioning
confidence: 99%